Professional Influence of Teachers in the Understanding of Mathematical Structures on Learning Outcomes in Terms of Social Emotional Competence - Riyadi Riyadi; Sandra Kurniawan; Anesa Surya (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract The purpose of this study was to examine the professional influence of teachers in understanding the structure of mathematics on learning outcomes in terms of social emotional competence. This type of research is quantitative with an experimental approach. The population is teachers and students of Class V in Wonogiri district. Sampling technique with cluster random sampling technique. Data collection techniques through: social emotional questionnaire and mathematical structure, as well as tests. Data analysis using Anava two way with same cell and Anava further test. The results of this study showed that F account (90.416) is greater than F table (3.84), meaning that the teacher's professional influence on the learning outcomes of mathematics and F account (28.605) is greater than F table (3.00), social emotional competence influence on learning outcomes mathematics. The conclusion of the study is that professional teachers in understanding the structure of mathematics and social emotional competence of learners affect learning outcomes, namely increased understanding of mathematical concepts. The implication of this study is that the professional competence of teachers in understanding the structure of mathematics and social emotional competence of learners to be one of the determining variables in setting an effective mathematical learning model for the achievement of learning outcomes.